The Implications of 'Zeroing' on Enforcement of U.S. Antidumping Law - William W. Nye (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2008)
The United States and other countries enforce their antidumping regulations in roughly the same way. There is a difference, however. The United States–but not other countries–now uses 'zeroing' in its determination of whether imports are dumped. The use of 'zeroing' will almost always increase the level of any antidumping duty, and will sometimes create a duty where none would have been imposed, had the methodology not been used. All countries test for dumping by attempting to determine whether imports are being sold at less than 'normal' value. Other countries do this by simply comparing the average price at which the product is sold in the country of production with the average price at which the same product is sold in the importing market. If the average of the observed prices in the importing country is lower than the average price in the country of production (the 'normal' value), then the foreign firm is said to be dumping. Using zeroing, however, the U.S. treats import price observations above the 'normal' value as if they occurred at the 'normal' value (rather than at their observed level). Transactions at prices below the normal value are treated at their observed levels. The result of zeroing has been to make the U.S. antidumping laws more restrictive than they might appear, with a positive antidumping margin potentially being found if any single transaction occurs below 'normal' value, even if the average of the import prices in the U.S. is much higher than the 'normal' value. The U.S. practice of zeroing has recently been challenged at least six times before the World Trade Organization (WTO), and has generally been found to be inconsistent with the WTO obligations of the United States. The net impact of the zeroing methodology on the United States (compared to antidumping enforcement without zeroing) depends inter alia on the dispersion of the U.S. prices obtained by foreign exporters under dumping investigation. No real estimates of this dispersion exist, but the paper discusses some related evidence which may permit an inference. This evidence is itself quite dispersed, and, therefore, an estimate of the impact and cost of zeroing to the United States has a broad range of uncertainty. But it is plausible that zeroing could add perhaps 3-4 % to the typical U.S. antidumping duty with a cost to the U.S. of around 150 million per year when all existing U.S. antidumping orders were determined by zeroing.
Keywords: F13; 330; Trade; Dumping; Import; Zeroing; United States; WTO